Goals and content of public private partnership - Брайловський, Ілля Аркадійович (Technology audit and production reserves, 2014)
The paper analyzes the goals and content of public private partnership (PPP) as well as identifies benefits for parties which implement such agreements. The main features and application fields of PPP are indicated. It is emphasized that despite the difference in goals (a private partner strives to obtain a stable profit whereas the state in interested in increasing the scope and improving quality of services delivered by infrastructural and socially focused industries to population and economic agents), the parties to PPP agreements reach a compromise in resolving strategic objectives and mitigating social conflicts. It is demonstrated that an important prerequisite for motivating the private sector to join PPP is abidance by clear legal formal rules in the institutional system. Research results may be used by economists and public administration specialists in designing development programs of territorial entities of different levels (regions and the country as a whole).